Regesten Kaiser Sigismunds (1410-1437), Band 2 Die Urkunden und Briefe aus den Archiven und Bibliotheken West-, Nord- und Ostböhmens - Elbel, Petr (2016)
The volume contains the edition of 180 abstracts of the charters and letters from the archives and libraries in West, North and East Bohemia, issued by Emperor Sigismund (1410-1437). It is the second volume of the planned complete revision of the edition of abstracts "Urkunden Kaiser Sigmunds" (Innsbruck 1896/1900) published by Wilhelm Altmann within the framework of the Regesta Imperii. The volume includes a large historical introduction, a bibliography and an index and adds primarily to the historical documentation of the major cities of Eger/Cheb, Pilsen/Plzeň and Elbogen/Loket in West Bohemia which remained loyal to the king during the Hussite Revolution, and sheds light on the career, estate property and diplomatic forgeries of Sigismund's influential chancellor Kaspar Schlick, a burgher of Eger.